'HIS WALKING ISN'T RIGHT DOCTOR': A CASE OF HYDROCEPHALUS PRESENTING AS AN ABNORMAL GAIT. Issue 11 (9th October 2013) - Baker, John
Abstract : Introduction: Hydrocephalus can present in a number of different ways in adult patients. Most typically these include headache and impaired cognition, or cranial nerve palsies. In this case a patient presented more atypically with lower limb spasticity and an abnormal gait that had developed insidiously over a number of years. This was initially diagnosed as a case of transverse myelitis with a Brown–Sequard syndrome. A literature review identified only a couple of previous case reports of hydrocephalus presenting in this way without a clear history of impaired cerebration. 1 Case Description: A 41 year old was referred by his GP after his wife had become concerned that his walking had become awkward. He was stiff and unsteady and had a recent history of tripping and stumbling. He denied any upper limb symptoms and there was no history of any bowel or bladder abnormalities. On examination he had a stiff/spastic gait; reflexes were brisk bilaterally with some clonus. However, plantar responses were flexor in both feet. There was diminished proprioception on the right side and a reduction in pinprick sensation on the left side up to a high thoracic level. A provisional diagnosis of transverse myelitis with a Brown–Sequard syndrome was made. Blood tests and scans were requested. An MRI brain scan identified significant dilatation of the latreral and third ventricles. A diagnosis of non–communicating hydrocephalus was made. The patient was referred to the neurosurgical team was managed with a ventriculostomy. He was reviewed after three months and had improved significantly. Discussion and Conclusions: This case illustrates one of the manifold ways in which hydrocephalus can present. These include changes in heart rate and respiratory rate, confusion, cranial nerve palsies, and abnormalities of motor function. When assessing a patient with a spastic gait there are a number of pathologies to be considered. It is important not to forget to consider hydrocephalus as this is a potentially chronic and progressive cause that has a significant mortality but for which there is a definitive surgical management option that can lead to a complete resolution of symptoms.